Gurukul Education and Its Impact on Modern Education - Adhikari, Toya Nath (Shiksha Shastra Saurabh, 2022)
Education has played important role in the expansion of civilization in the world today. Similarly, in the context of education, Gurukul education is known as the oldest system of education. It is mostly true that education in the world got its root in the Gurukul education system. Our ancient Vedas, Purans, and Upanishads were written through the skills obtained from the Gurukul education system which are sources of vast knowledge. So, Gurukul education has played a major role in the transformation of modern education systems. So, the purpose of this research study is to present the impact of Gurukul education in building modern education in this form. This research study is a qualitative study and data are collected through interview-based on fieldwork and document analysis. The interview is taken faceto-face with teachers and students of Gurukul schools located in Chitwan, Nepal.The finding of this study show that Gurukul education is the root of all knowledge created by our ancient saints (Munis) and it has certainly got an impact on the present modern education. In modern education systems, there are traces of the education systems to bring transformation as we find today. This study has got practical implications for the development of modern education showing the relation between Gurukul and modern education.